Strategi Komunikasi Akun Instagram @Gen.Saladin dalam Menyebarkan Pesan Dakwah Berbasis Sejarah - Siti Rohmah; Salis Irvan Fuadi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Utilizing social media platforms like Facebook, Instagram, and Twitter are media that are considered effective in spreading Islamic da'wah because they are easy to access at anytime and anywhere so that the spread of Islamic da'wah can be done quickly with a wide audience reach. In managing social media, a communication strategy is needed so that the goal of disseminating information can be achieved. The purpose of this study is to ascertain the communication tactics used by the Instagram account @gen.saladin to disseminate da'wah. The method used in this kind of research is qualitative descriptive. Interviews and documentation are used in data collection methods. This study's analysis makes use of Milles and Huberman's methodology, which includes data reduction, data presentation, and findings.The study's findings demonstrate that the communication strategy used by the Instagram account @gen.saladin is predicated on Lasswell's idea of "Who Says What in Which Channel to Whom With What Effect?" and entails actions like gaining a thorough grasp of the target audience, content production interesting and relevant, consistency in posting, active interaction with followers, appropriate use of hashtags and tagging, utilizing Instagram features, regular measurement and evaluation, and collaboration with influencers and other communities.